2009
DOI: 10.2337/dc08-1968
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Maintenance of Treatment Outcomes: Diabetes Personal Trainer Intervention for Youth With Type 1 Diabetes

Abstract: OBJECTIVE -To describe a 2-year follow-up of A1C outcomes of a self-regulation intervention for youth with type 1 diabetes.RESEARCH DESIGN AND METHODS -A total of 81 youths with type 1 diabetes ages 11-16 years were randomized to usual care versus a diabetes personal trainer intervention consisting of six self-monitoring, goal-setting, and problem-solving sessions with trained nonprofessionals. A1C data were obtained from medical records 2 years postintervention, and ANCOVA adjusting for age and baseline A1C w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 9 publications
0
47
0
4
Order By: Relevance
“…Interventions to improve treatment adherence specifically targeting transplant recipients in this age period may help improve outcomes. Such interventions may include enhanced social and/or nursing support (51), technologies such as text-message dose reminders (52), the use of health coaches (53,54), or some combination of these (55).…”
Section: Discussionmentioning
confidence: 99%
“…Interventions to improve treatment adherence specifically targeting transplant recipients in this age period may help improve outcomes. Such interventions may include enhanced social and/or nursing support (51), technologies such as text-message dose reminders (52), the use of health coaches (53,54), or some combination of these (55).…”
Section: Discussionmentioning
confidence: 99%
“…In that study, a significant improvement in glycemic control relative to the control group was obtained and maintained 2 years after intervention for the older participants but not for the younger participants. 27,43 The WE-CAN approach used in this study was delivered to parent and child together and incorporated greater attention to parentchild issues. We anticipated that these changes would make the intervention more effective for youth across the age range; however, findings in this study were virtually identical to those observed previously, suggesting that this approach may be most salient for youth who are beginning to take greater responsibility for their diabetes management.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that behavioral interventions hold promise for addressing these factors and improving diabetes management in youth. 17,18,[22][23][24][25][26][27][28][29][30][31] Findings have yet to result in the translation of behavioral intervention into standard clinical care, however. Barriers include reimbursement issues, staff training, and the reality that most behavioral interventions were not designed for integration into clinical care.…”
mentioning
confidence: 99%
“…Two domains of outcome measures were extracted: diabetes functioning/medically performing/HbA1c and psychosocial functioning. Studies were excluded if they involved improving education alone, had no explicit theoretical background, 6,7,[44][45][46] were not a RCT, 15,[46][47][48][49][50] included children only 51,52 or adults 53 54 ) were checked in order to capture other relevant publications (see Appendix A for search terms at www.bjd-abcd.com).…”
Section: Eligibility Criteriamentioning
confidence: 99%